TEACHERS’ COOPERATION WITH PARENTS OF STUDENTS WITH SPECIAL EDUCATIONAL NEEDS - Kaffemanienė, Irena; Tomėnienė, Laima; Verpečinskienė, Fausta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Teachers’ cooperation with parents of students with special educational needs (SEN) is particularly important for students with special educational needs. Theoretical analysis has found that there are often problems of cooperation between teachers and parents of children with special educational needs. In order to clarify this, a quantitative study was carried out. The research aim – to reveal the peculiarities of cooperation between teachers and parents of students with special educational needs. The method of a questionnaire survey was chosen for the research, a questionnaire of semi-closed questions was created. The study involved 353 general education teachers. The results of the teacher survey showed that parents are not sufficiently involved in the process of cooperation. The most common forms of cooperation between teachers are individual consultations. The majority of the teachers indicated that they usually cooperate with parents of students with SEN in solving teaching/learning problems of the child, less often they cooperate in developing an individual curriculum. According to the respondents, the main problems are different understanding of responsibilities and demands of teachers and parents on each other.